PENERAPAN METODE HIWAR NABAWI DALAM MENINGKATKAN HASIL BELAJAR FIKIH DI KELAS VIII MTS AL-FALAH RUPAT - Hakim, Lukman; Robi'ah, Robi'ah (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This research was motivated by the application of the hiwar nabawi method in improving fiqh learning outcomes in class VIII MTs Al Falah Rupat. This research aims to determine the application of the Hiwar Nabawi method and determine the inhibiting factors in the application of the Hiwar Nabawi method in improving class VIII Fiqh learning outcomes at MTs Al-Falah Rupat. This type of research is experimental research, namely by collecting data using documentation tests. The data collection techniques used by researchers to obtain research results use posttest and pretest, normality test, T-test sample test and documentation. The research results show that the application of the Hiwar Nabawi method is very helpful in learning because it makes students quite effective. Judging from the results of the Paired Sample T-Test, it shows that the significance level is 0.000 <0.05, which means it is significant. While the t value is -13.766 < -1.72913, it is concluded that Ha is accepted and H0 is rejected. It can be interpreted that there is a negative and significant influence on the pretest and posttest results. Thus, it can be said that there is a significant influence on the implementation of the Hiwar Nabawi method. Then in implementing the learning method there are obstacles such as students who are quiet, embarrassed to express words. The number of samples in this research was 21 students of class VIII MTs Al-Falah Rupat